Modeling Multiattribute Utility, Risk, and Belief Dynamics for New Consumer Durable Brand Choice - Roberts, John H.; Urban, Glen L. (Management Science, 1988)
This paper proposes a brand choice model to aid in the prelaunch management of a new consumer durable entry in an existing category. The model contributes to theory by integrating the critical phenomena of multiattribute preference, risk, and dynamics in an individual level expected utility framework. The integration is based on established theoretical constructs in utility, Bayesian decision analysis, and discrete choice theory. Measurement and estimation procedures are presented, an application is described, and the managerial relevance of this work as a planning and forecasting tool is examined.